Numerical evaluation of structural concrete insulated panels for thermal energy efficient buildings - Ahmed, Sohaib; Khitab, Anwar (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study is focused on thermal evaluation of Structural Concrete Insulation Panels (SCIPs) as building material. In Pakistan energy shortage is one of major issues since the last decade. As buildings consume more than 40 % of total production of electrical energy, it is necessary to innovate, analyse and apply various energy saving and optimization techniques for constructing thermal energy efficient buildings. SCIPs consist of three layers, in which a central polystyrene foam is sandwiched between two concrete layers. SCIPs are available in flexible sizes ranging from 0.3-1.2 m in width and 2.4-3.0 m in length. Owing to their light weight and easy fabrication, they are suitable for remote areas and severe weather conditions. In this study, numerical approach is used to compare the thermal performances of SCIPs and ordinary concrete incorporated walls in a school building system. Hourly recorded data of dry-bulb and dew-point temperatures of surface, humidity and mean air temperatures are used in simulation. Data for one typical year are used to compare the energy requirements of building made of ordinary concrete and SCIPs walls with expanded polystyrene as insulation material. Simulation results were acquired by means of EnergyPlus software and are presented to evaluate the heating and cooling demands of energy for a year. Study reveals that the SCIP walls incorporated buildings have a greater energy efficiency, reduce energy demand by 25% and HVAC systems by 20 % for assigned thermal zone.